2009
DOI: 10.1258/ijsa.2009.009238
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intimacy predicts condom use: findings in a group at high sexually transmitted disease risk

Abstract: Previous studies have reported an inverse relationship between condom use and emotional intimacy. The aim of this study was to determine the relationship between condom use and emotional intimacy. The study was a gonorrhoea case-comparison study with the samples being drawn from public health clinics (cases) and select bars/nightclubs (places) of Houston, TX (n = 215). Data were collected by questionnaires administered on a laptop computer. The majority of respondents were African-American (97.7%), women (69.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Other studies have shown low condom use to be related to a wide variety of factors, including decreased sensation, partner disapproval, non-communication, low levels of emotional intimacy and alcohol use [15], [33], [34], [35]. Höglund et.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown low condom use to be related to a wide variety of factors, including decreased sensation, partner disapproval, non-communication, low levels of emotional intimacy and alcohol use [15], [33], [34], [35]. Höglund et.…”
Section: Discussionmentioning
confidence: 99%
“…Women in this study presented risk factors that could predispose them to STI acquisition, including low educational levels (≤9 years of school; 52%), initiation of sex before age 18 years (70%), more than three sexual partners in their lifetime (10%), and economic dependence and long-term partner relationships. Length of partner relationship was found to be negatively associated with condom use (Damani et al, 2009;Exavery et al, 2012;Varela Arévalo et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Length of relationship was negatively correlated with condom use (Damani et al, 2009;Exavery et al, 2012;Varela Arévalo et al, 2011). This finding may reflect cultural and gender norms, such as the belief that housewives are safe in the marriage relationship, so that they do not request condom use with their partners, even when they suspect that the partner has had another sexual partner (Gómez Alvarez & Fonseca Hernández, 2012;Ragsdale, Gore-Felton, Koopman, & Seal, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Nightclubs and nightlife also cause concern due to their potential negative impacts on society and have become a context for studying various problems: drugs, alcohol, tobacco and drugs [88][89][90], violent behavior [91][92][93], risky sexual intercourse [94,95], accidents or disasters [96,97] and health problems [79,98]. Social behavior has also been analyzed in the context of nightlife [99][100][101][102], but studies are scarcer from the management field [103][104][105][106][107].…”
Section: Nightlifementioning
confidence: 99%